Validation of the use of a fluorescent PARP1 inhibitor for the detection of oral, oropharyngeal and oesophageal epithelial cancers - Kossatz, Susanne; Pirovano, Giacomo; Demétrio De Souza França, Paula; Strome, Arianna L.; Sunny, Sumsum P.; Zanoni, Daniella Karassawa; Mauguen, Audrey; Carney, Brandon; Brand, Christian; Shah, Veer; Ramanajinappa, Ravindra D.; Hedne, Naveen; et al. (Nature biomedical engineering, 2020)
For oral, oropharyngeal and oesophageal cancer, the early detection of tumours and of residual tumour after surgery are prognostic factors of recurrence rates and patient survival. Here, we report the validation, in animal models and a human, of the use of a previously described fluorescently labelled small-molecule inhibitor of the DNA repair enzyme poly(ADP–ribose) polymerase 1 (PARP1) for the detection of cancers of the oral cavity, pharynx and oesophagus. We show that the fluorescent contrast agent can be used to quantify the expression levels of PARP1 and to detect oral, oropharyngeal and oesophageal tumours in mice, pigs and fresh human biospecimens when delivered topically or intravenously. The fluorescent PARP1 inhibitor can also detect oral carcinoma in a patient when applied as a mouthwash, and discriminate between fresh biopsied samples of the oral tumour and the surgical resection margin with more than 95% sensitivity and specificity. The PARP1 inhibitor could serve as the basis of a rapid and sensitive assay for the early detection and for the surgical-margin assessment of epithelial cancers of the upper intestinal tract. A fluorescently labelled inhibitor of the DNA repair enzyme poly(ADP–ribose) polymerase 1 is used to detect epithelial cancers of the upper intestinal tract in animals, in biopsied human tissue and in a human patient.